2010
DOI: 10.1111/j.1442-2042.2010.02525.x
|View full text |Cite
|
Sign up to set email alerts
|

Benign pathological findings in 303 Chinese patients undergoing surgery for presumed localized renal cell carcinoma

Abstract: Objective: To analyze the incidence of benign lesions in Chinese patients undergoing nephrectomies for renal masses identified as localized renal cell carcinoma (RCC) in preoperative imaging. Methods: Between 1999 and 2007, 303 patients (112 female, 191 male) with presumed localized RCC underwent nephrectomy (234 radical nephrectomies and 69 partial nephrectomies). Preoperative computed tomography images and pathological findings were reviewed and analyzed. Results: Pathological examinations revealed 31 (10.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 11 publications
6
27
1
Order By: Relevance
“…Previous studies indicated that 12.4-30.0% of tumors smaller than 2 cm were benign compared with 4.8-20.9% of those larger than 2 cm in cases with small renal masses presumed to be T1a RCC (5,6,(19)(20)(21)(22)(23). Furthermore, the incidence of benign pathological lesions in the renal tumors of ≤20 mm in diameter was significantly higher (12.7%) than in tumors >20 mm (3.9%) in the present series.…”
Section: B C D a F Econtrasting
confidence: 47%
See 3 more Smart Citations
“…Previous studies indicated that 12.4-30.0% of tumors smaller than 2 cm were benign compared with 4.8-20.9% of those larger than 2 cm in cases with small renal masses presumed to be T1a RCC (5,6,(19)(20)(21)(22)(23). Furthermore, the incidence of benign pathological lesions in the renal tumors of ≤20 mm in diameter was significantly higher (12.7%) than in tumors >20 mm (3.9%) in the present series.…”
Section: B C D a F Econtrasting
confidence: 47%
“…Fujii et al suggested that one possible reason for the lower incidence of benign pathological findings in Asian than Western countries was the low incidence rate of oncocytoma in Asia (7), which is indistinguishable from RCC using the present imaging modalities (24). The reported incidence rates of oncocytoma in small renal masses were 5.7-10.7% in Western countries (5,6,19-22) but 1.3-2.8% in Asian countries (7,8,23), consistent with the results of the present study (1.5%). Although further studies in various countries are required, these observations suggest that there may be ethnic differences in the oncocytoma incidence rate.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Renal angiomyolipoma usually contains significant fat and therefore, shows typical characteristics of fat on CT or MRI. The differential diagnosis of renal carcinoma is usually not difficult, but lesions with little or no fat and small tumors are difficult to discern on conventional CT, plain MRI and contrast-enhanced imaging (3)(4)(5). In addition, certain patients are allergic to the contrast material used during enhanced CT (6,7).…”
Section: Introductionmentioning
confidence: 99%